Basic principles and diagnostic of colposcopy - Heru Pradjatmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACTThe colposcope is an optical system that offers illumination and magnifications between 10 and 16 times. Colposcopy is the diagnostic test to evaluate patients with an abnormal cervical cytological smear, abnormal VIA (visual inspection with acetic acid application) or VILI (visual inspection with Lugo’s Iodine application), abnormal appearing cervix and directing biopsies. The colposcopic examination of the cervix starts with “General Assessment” to immediately recognize the level of examination reliability. Examination should assessed for three variables: 1) adequate or inadequate, with the reason given; 2) squamocolumnar junction visibility; and 3) transformation zone type. Colposcopic features and patterns will correspond with underlying specific histological features. The greater the expertise and experience of the colposcopist, the greater the confidence in the assessment of the atypical transformation zone (TZ). For practical purposes, the most important aspect is always the recognition or exclusion of underlying actual invasive disease. The presence or absence of precancerous lesions can confirm with colposcopy.